Creativity Development of High-Achieving Students. Issue 3 (3rd July 2019) - Hemdan, Ahmed Hassan; Kazem, Ali Mahdi
Abstract : Few studies on creativity have focused on creativity development in various grade levels for high-achieving students. The purpose of this study was to explore the developmental trajectories of creative ability for high-achieving students. The participants constituted a national representative sample of 982 male (N = 506) and female (484) students from grades 1 to 10 in five governorates in Oman (Muscat, South-Al Batinah, South- Al Sharqia, Dhofar, and Al Dhakilia). The students completed two subtests of the Profile of Creative Abilities (PCA), a measure of creative potential, namely drawings and categories. There was an evidence of a developmental trend of creativity across grade levels. The Multi-variate analysis of variance (MANOVA) showed that the main effect of grade was statistically significant for the drawings subtest. Also, the main effect of gender was also statistically significant for the drawings subtest. The main effect of interaction (gender X grade) was not significant. Overall, females' creative performance was significantly better than males' in the Creativity Index score. The results of the study are discussed in the light of existing literature about developmental trends and gender differences in creative thinking.